ANALISIS STRUKTUR PEREKONOMIAN DAN FAKTOR-FAKTOR YANG MEMENGARUHI PERTUMBUHAN EKONOMI SUMATERA SELATAN - Indrayansyah Nur; Sri Mulatsih; Alla Asmara (IPB University, 2013)
This study aims at analyzing the structure of the economic growth in the province of South Sumatera and the factors that influence the economic growth in the region. The method to analyze the economic structure is a regional economy approach using Location Quetiont (LQ) method and Shift Share (SS) Analysis. The National Share (NS) component indicates that the higher values are the sectors on mining and minerals, agriculture and manufacturing industry. Thus, those three sectors are strongly influenced by the change in national policy. The Industry Mix (IM) component indicates that the higher values are on the sectors on transportation and communication, construction and trade, and hotel and restaurant. That indicates that those three sectors have higher growth than other sectors. The Regional Share (RS) component indicates that agriculture is the dominant sector and therefore the most competitive sector compared to industries in the national level. It is also revealed that the progressive sectors during 2001-2005 are trading, hotel, restaurant, and construction and during 2005-2010 are service firms, finance, rental, trading, hotel, and restaurant. Using LQ analysis, the base sectors in South Sumatera during 2001-2010 are mining and minerals, agriculture, and construction. On the whole, the variables of PMA, PMDN, goverment expenditure and labor force simultaneously influence the PDRB as high as 85%. In partial view, PMDN, goverment expenditure and labor force have significant and positive influence toward PDRB, as indicated by a small probability value. Meanwhile, PMA has insignificant and negative influence toward PDRB. Keywords: shift-share, location quotient, labor force, government expenditure